2018
DOI: 10.1007/s11118-018-9705-7
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Transformation on Metric Measure Spaces

Abstract: We study several problems concerning conformal transformation on metric measure spaces, including the Sobolev space, the differential structure and the curvature-dimension condition under conformal transformations. This is the first result about preservation of lower curvature bounds under perturbation, which is new even on Alexandrov spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We also would like to mention the follow-up work by Bang-Xian Han and Anna Mkrtchyan [10] which extend several results of this paper to the setting of metric measure spaces without 'smoothness' assumptions.…”
mentioning
confidence: 63%
“…We also would like to mention the follow-up work by Bang-Xian Han and Anna Mkrtchyan [10] which extend several results of this paper to the setting of metric measure spaces without 'smoothness' assumptions.…”
mentioning
confidence: 63%
“…Combining the techniques and results in [14,20], the first author [15,16] proved the transformation formula for the Lagrangian curvature-dimension condition RCD(K, N) under conformal transformation when the reference function w is bounded and smooth…”
Section: Remarkmentioning
confidence: 99%
“…Combining the techniques and results in [ 14 , 20 ], the first author [ 15 , 16 ] proved the transformation formula for the Lagrangian curvature-dimension condition under conformal transformation when the reference function w is bounded and smooth enough. Together with the well-known transformation formula for under drift transformations, this result also provides a transformation formula for under time change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the outcomes of the tensor calculus on RCD spaces built in [4] is the existence of a measure-valued Ricci tensor. An example of application of this object to the study of the geometry of such spaces is given by the paper [7] where, inspired by some more formal computations due to Sturm [15], it is shown that transformations of the metric-measure structure (like, e.g., conformal ones) alter lower Ricci curvature bounds as in the smooth context.…”
Section: Introductionmentioning
confidence: 99%